2020
DOI: 10.1016/j.psj.2019.10.048
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the impact of gut microbiotas on fertility of stored sperm by types of hens

Abstract: Owing to the practical interest in understanding duration of fertility ( DF ) to reduce the cost of producing hatching eggs by decreasing the frequency of artificial insemination, as well to uncover the mechanism of the estrogen-gut microbiome axis, elucidating the interaction between the maternal microbiome and the function of sperm storage tubules ( SST ) has become important for revealing the DF in laying hens. In this study, we investigated the compositional, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Through a symbiotic relationship with the host, bacteria can produce essential amino acids and vitamins and regulate digestion to shape host health and function. In poultry research, the pattern diversity of gut microbiome communities has been used as a novel molecular marker to explore the microbiome associated with candidate performance, including weight gain ( Elokil et al, 2022 ), egg production ( Elokil et al, 2020a ), immunity ( Elokil et al, 2020c ), and fertility ( Elokil et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Through a symbiotic relationship with the host, bacteria can produce essential amino acids and vitamins and regulate digestion to shape host health and function. In poultry research, the pattern diversity of gut microbiome communities has been used as a novel molecular marker to explore the microbiome associated with candidate performance, including weight gain ( Elokil et al, 2022 ), egg production ( Elokil et al, 2020a ), immunity ( Elokil et al, 2020c ), and fertility ( Elokil et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, gut microbiota secures the permeability of the intestinal mucosa and regulates the fermentation and absorption of dietary nutrients, which may explain the microbiota importance in the regulation of energy and growth activities (Sonnenburg and Bäckhed, 2016). In our previous studies, we investigated some factors that affect gut microbiota development in chicken, including performance type (Elokil et al, 2020a), medicine (Elokil et al, 2020b), fertility (Elokil et al, 2020a), and diet (Abouelezz et al, 2019). The FMT has been reported as the most effective way for whole microbial community changes, whereas probiotic and antibiotic tools usually alter up to three orders of the 100 trillion native microorganisms of the gut (Borody and Khoruts, 2012;Cammarota et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research confirmed the presence of microorganisms in the maternal reproductive tract and digestive tracts of 1-day-old chicks ( Pajurek et al, 2019 ; Zhou et al, 2021 ). Several studies have shown that hen gut and fecal microbes are associated with both egg formation and fertility ( Elokil et al, 2020a , b ). This suggests that microbes may have an effect on the reproductive traits or eggs of the hens.…”
Section: Introductionmentioning
confidence: 99%